2017
DOI: 10.1016/j.neuroscience.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing anti-interleukin-1β antibodies reduce ischemia-related interleukin-1β transport across the blood–brain barrier in fetal sheep

Abstract: Hypoxic ischemic insults predispose to perinatal brain injury. Pro-inflammatory cytokines are important in the evolution of this injury. Interleukin-1β (IL-1β) is a key mediator of inflammatory responses and elevated IL-1β levels in brain correlate with adverse neurodevelopmental outcomes after brain injury. Impaired blood-brain barrier (BBB) function represents an important component of hypoxic-ischemic brain injury in the fetus. In addition, ischemia-reperfusion increases cytokine transport across the BBB of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 63 publications
(125 reference statements)
0
25
0
Order By: Relevance
“…In the short-term, it can result in seizures and an encephalopathy, and long-term it can result in cerebral palsy, impairments in hearing and vision, cognitive impairments, and problems with attention and irritability. In utero brain ischemia induces proinflammatory events, including increased increases in IL-1 β and IL-6 in the brains of both mothers and their fetuses ( Sadowska et al, 2012 ), opening of the fetal BBB, and increased cytokine transport into the fetal brain ( Chen et al, 2012 ; Sadowska et al, 2015 ; Patra et al, 2017 ). That these cytokine elevations are causal to brain damage is illustrated by the ability of blocking antibodies directed against IL-1 β and IL-6 to reduce cytokine transport across the BBB, reduce cytokine levels in brain, and attenuate or reverse BBB disruption ( Chen et al, 2015 ; Zhang et al, 2015 ; Patra et al, 2017 ).…”
Section: Physiologic Conditions Disease States and Pharmacologimentioning
confidence: 99%
“…In the short-term, it can result in seizures and an encephalopathy, and long-term it can result in cerebral palsy, impairments in hearing and vision, cognitive impairments, and problems with attention and irritability. In utero brain ischemia induces proinflammatory events, including increased increases in IL-1 β and IL-6 in the brains of both mothers and their fetuses ( Sadowska et al, 2012 ), opening of the fetal BBB, and increased cytokine transport into the fetal brain ( Chen et al, 2012 ; Sadowska et al, 2015 ; Patra et al, 2017 ). That these cytokine elevations are causal to brain damage is illustrated by the ability of blocking antibodies directed against IL-1 β and IL-6 to reduce cytokine transport across the BBB, reduce cytokine levels in brain, and attenuate or reverse BBB disruption ( Chen et al, 2015 ; Zhang et al, 2015 ; Patra et al, 2017 ).…”
Section: Physiologic Conditions Disease States and Pharmacologimentioning
confidence: 99%
“…We examined the cerebral cortex as it represents an important brain region, and because we had residual frozen frontal cerebral cortical samples from our previous studies [4,[29][30][31]. We have recently published a detailed schematic that we have used for our brain sample preparation in similar studies [32].…”
Section: Animal Preparation Study Groups and Experimental Designmentioning
confidence: 99%
“…A coronal brain section of another half of the fetal brain was obtained at the level of the hypothalamus (mammillary bodies) for histopathological analysis [32]. The residual frozen brain from the frontal cortex was saved and used in prior publications [4,29,31,32] and for the current study in order to maximize information obtained from this complex large animal resource. Unfortunately, although we have previously measured BBB permeability and tight junction proteins in some of the fetal sheep reported in the current study, we did not have sufficient residual tissue remaining from the sham control animals.…”
Section: Animal Preparation Study Groups and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β is the earliest inflammatory cytokine that occurs after HIE hypoxic ischemic brain damage, and is also the key medium in the immunoregulation of neuroendocrine system. [7] Patra et al [8] have found that neonatal hypoxic and ischemic injury is an important cause of perinatal brain damage. Proinflammatory cytokines play an important role in the evolution of this brain injury.…”
Section: The Characteristics Of Hie In Perinatal Neonatesmentioning
confidence: 99%